Analysis of The Competitiveness of Indonesian Coffee in The Export Market - Rahayu Widyantini (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
Coffee is one of the Indonesia's leading products. It contributed to 2.7% of the world's exports and ranked number fourth as the world coffee producers in 2018. Indonesian coffee export has declined during the 2014-2018 at 5%. Similarly, production capacity has decreased too by 5.6% from 2017-2018. The global value chain for coffee is dominated by a relatively small number companies, mostly comes from foreign companies. As the result, the stakeholders involved in the coffee industry are not is not performing in the maximum result for expanding the overall value produced. This study aims to understand the competitiveness of Indonesian coffee in global market using the Revealed Comparative Advantage (RCA) and the Diamond Porter’s theory. This study utilized secondary data to calculate the RCA index and descriptive data from government report to explain the Diamond Porters theory. The results show that Indonesian RCA index is about 2,8 in 2018. The RCA value index is above the value of 1, means that Indonesia has good competitiveness in the global market. Based on this qualitative analysis, internal factor shows that Indonesia has a lower productivity as compared to the other top four exporting countries. Total demand of Indonesian coffee export is fluctuated but domestic demand shows an increase trend. There are only six big local company that processed additional values to the coffee. The Indonesia export destination country is also shown as the competitive market.